Enhancing Service Personnel’s Emotional Labour Techniques: An Empirical Case for Spiritual Intelligence - Ogunsola, Kazeem Olanrewaju; Fontaine, Rodrigue Ancelot Harvey; Jan, Mohammad Tahir (UNISSULA, 2020)
The paper aims to examine the relationship between emotional labour (EL) techniques of surface acting (SA) and deep acting (DA) with spiritual intelligence (SQ). Building on Multiple Intelligence Theory (MI), 373 service personnel, mainly teachers, were drawn through a list-based simple random sampling, from 30 secondary schools around Peninsular Malaysia. Structural equation modeling (SEM) was used to test the hypotheses, and the proposed model was assessed through renowned model fit indices. Findings revealed that SQ buffers EL costs, as both SA and DA routine became positively related to SQ. Proposed model had reasonable fit indices with χ² / df ratio (1002.288 / 336) = 2.983, RMSEA (0.078) and CFI (0.931). Providing empirical support to the hypotheses that EL performance tends resonate well with spiritual intelligent service personnel. The adequacy of this paper’s findings is vital as it cut across all Faiths. Practically, it tends to stimulate service personnel towards a higher degree of self-awareness and imbue them with the capacity to be flexible, face and transcend pain and suffering. Socially, it sustains a friendly and cordial interpersonal relationship with others (customers). Policy wise, it informs organizations to re-align HR strategies to capture ‘Type B’ personalities. Theoretically, it stirs more research on SQ as it affects service personnel’s organizational behaviours. The paper is cross-sectional and limited to one group of service personnel (teachers). Future study may consider other groups to ascertain the generalisability of these findings. While augmenting body of knowledge on organizational behaviour, the study is pioneered as the first to propose SQ to buffer EL costs, in order to enhance SA and DA techniques.